Group Buying on the Web: A Comparison of Price-Discovery Mechanisms - Anand, Krishnan S.; Aron, Ravi (Management Science, 2003)
Web-based group-buying mechanisms are being widely used for both business-to-business (B2B) and business-to-consumer (B2C) transactions. We survey currently operational online group-buying markets, and then study this phenomenon using analytical models. We build on the literatures in information economics and operations management in our analytical model of a monopolist offering Web-based group-buying under different kinds of demand uncertainty. We derive the monopolist's optimal group-buying schedule under varying conditions of heterogeneity in the demand regimes, and compare its profits with those that obtain under the more conventional posted-price mechanism. We further study the impact of production postponement by endogenizing the timing of the pricing and production decisions in a two-stage game between the monopolist and buyers. Our results have implications for firms' choice of price-discovery mechanisms in e-markets, and for the scheduling of production and pricing decisions in the presence (and absence) of scale economies of production.